The perception of political representation of the Malay-Muslim community in Singapore - Mohamed Salihin Subhan (2018)
In 2016, the Singapore government reserved the Presidential Elections for the Malay-Muslim community ostensibly to ensure the representation of minority ethnic groups, sparking debate on the political representation of the Malay-Muslim community. This dissertation puts forth the argument that the Singapore government’s policy of multiculturalism has negatively affected the perception of political representation of the Malay-Muslim community. Instead of empowering the community via descriptive representation, the government’s top-down approach has led to resentment. This negative perception within the community is analysed via the historical construction and contestation of Malay identity, with the Singapore government’s actions signifying a repeat of history. Looking forward, this dissertation identifies adaptive governance as a promising policy approach towards tackling the variegated nature of ethnic relations in Singapore.